Influence of Nano-Zinc Oxide on Physiological and Productivity Change of indica Rice - Samart, Sutichai; Phakamas, Nittaya; Chutipaijit, Sutee (Journal of Advanced Development in Engineering and Science, 2023)
The objective of this study was to determine the effect of zinc oxide nanoparticles (nano-ZnO) on yield of indica rice cv. Chainat 1. The experiment was conducted in the field of the Department of Plant Production Technology, Faculty of Agricultural Technology, King Mongkut’s Institute of Technology Ladkrabang during February to June, 2013. The experiment was laid out in Randomized Complete Block Design (RCBD) with 3 replications. Six rates of nano-ZnO were tested at the different concentrations i.e., 0, 100, 200, 400, 600 and 800 mg.L-1. Each rate of nano-ZnO was supplemented for every 14 days-interval until harvesting. The rice plants were collected at 72, 86, 100 and 114 days old. Leaf area index (LAI), number of panicles/clump, 1,000 seed weights, percentage of unfilled grain and harvest index (HI) were measured. The results showed that, the different concentrations of nano-ZnO were effect on plant growth and yield of rice. The additions of nano-ZnO at a rate of 200-400 mg.L-1 trended to promote leaf area index and harvest index greater than the other treatments. The application of nano-ZnO may be applied to other rice strains, including the other plant species in the future.